El cuento para el fortalecimiento de valores en niños de educación inicial 2 de la unidad educativa “Liceo Policial” ciudad de Riobamba, provincia de Chimborazo. - Salao Toapanta, Evelin Paola (2023)
The objective of this research project is to describe the work of stories to strengthen values in children of Initial Education 2 of the Educational Unit "Liceo Police" of the city of Riobamba- Chimborazo province. It is based on background and a theoretical framework created based on bibliographical references. The type of research that was used was descriptive and bibliographic since information on the two proposed variables was investigated through accurate, reliable sources to describe later and analyze them; likewise, observation was used as a technique for data collection, and an observation sheet was used as an instrument, which included 12 evaluation indicators and three assessment scales, the device was applied to 18 boys and girls of the initial 2 "A" of the Educational Unit "Police Lyceum." Finally, it can be concluded that once the importance and benefits have been analyzed, the story contributes positively to the strengthening of values in children, for which its constant use in early childhood education is of great importance since it offers multiple benefits to their development, encouraging children, boys, and girls to form their identity with principles and values from an early age.